Towards a Better Management of Decisional Big Data Systems: A Design Methodology - Mohamed Mehdi BEN AISSA; Lilia SFAXI; Riadh ROBBANA (Communications of International Proceedings, 2020)
Decisional systems are dedicated to support the decision-making activities, based on the available data in the organization. Decision-makers nowadays are more demanding in terms of accuracy, speed and availability of the analytics. This induces the need for complex platforms, managed by big teams and integrating data from various sources. Implementing these platforms requires a meticulous organization and a well-honed process that takes into consideration the team workforce, governance issues and agility requirements. In this context, we present a design methodology called DECIDE, intended for large-scale decisional Big Data projects.
Keywords: Data management; Design methodology; Distributed decision-making; Quality assurance; Big data applications.